Strategi Guru Akidah Akhlak dalam Meningkatkan Mutu Pendidikan Melalui Manajemen Pembelajaran di Mts Tahfidz Terpadu Anbata Medan - Latifah Hannum; Tumiran Tumiran; Nurhalima Tambunan (Education & Learning, 2026)
This study aims to examine teachers’ strategies for improving educational quality through learning management at MTs Tahfidz Terpadu Anbata Medan. The study employs a qualitative method with a descriptive approach. Data were collected through observations, interviews, and documentation. The findings indicate that the strategies implemented by Akidah Akhlak teachers in enhancing educational quality through learning management involve several stages. The planning stage includes the preparation of effective weeks, annual programs (Prota), semester programs (Promes), as well as the development of syllabi, lesson plans (RPP), and the analysis of Minimum Completeness Criteria (KKM). In the organizing stage, teachers align instructional materials with appropriate learning resources and media based on students’ characteristics and the school’s capacity. The implementation stage involves classroom management, the use of instructional strategies and approaches, the selection of learning media, and the application of various teaching methods to facilitate students’ understanding. The assessment or evaluation stage encompasses both process and outcome evaluation in the cognitive, psychomotor, and affective domains, including pre-tests, daily assessments, midterm examinations, and final examinations. Overall, these integrated stages of learning management contribute to improving the quality of education at the institution.